2009
DOI: 10.1159/000242477
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Loop between Plasminogen Activator Inhibitor-1 and Transforming Growth Factor-Beta1 during Renal Fibrosis in Diabetes

Abstract: Background/Aims: Plasminogen activator inhibitor (PAI)-1 is increasingly recognized as a profibrotic factor but the mechanisms are not entirely clear. The present study examined the profibrotic mechanism of PAI-1 focusing on its effect on transforming growth factor (TGF)-β1 in experimental diabetes. Methods: PAI-1 knockout (KO) mesangial cells cultured under high glucose (HG) in addition to streptozotocin-induced diabetic PAI-1 KO mice were used. Results: PAI-1 deficiency did not affect plasma glucose signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 72 publications
3
54
0
Order By: Relevance
“…On the other hand, the ECM is normally continually degraded and accumulation of ECM may also result from a deficit in ECM degradation. The plasminogen activation system is one of the most important degrading systems for the ECM (Eddy et al, 2006;Fogo, 2003) and several studies have shown that synthesis and deposition of the inhibitory protein PAI-1 are increased in the kidney during experimental and human nephropathies (Rerolle et al, 2000;Eddy et al, 2006;Seo et al, 2009). PAI-1 is also one of the targets regulated by TGF-b1 (Keeton et al, 1991).…”
Section: Figurementioning
confidence: 99%
“…On the other hand, the ECM is normally continually degraded and accumulation of ECM may also result from a deficit in ECM degradation. The plasminogen activation system is one of the most important degrading systems for the ECM (Eddy et al, 2006;Fogo, 2003) and several studies have shown that synthesis and deposition of the inhibitory protein PAI-1 are increased in the kidney during experimental and human nephropathies (Rerolle et al, 2000;Eddy et al, 2006;Seo et al, 2009). PAI-1 is also one of the targets regulated by TGF-b1 (Keeton et al, 1991).…”
Section: Figurementioning
confidence: 99%
“…As discussed above, the increment of plasmin and MMP-2 activity may have played a role in decreased fibronectin accumulation. On the other hand, PAI-1 can activate profibrotic protein synthesis via the uPA receptor [14,16]. We have also observed that recombinant PAI-1 stimulates TGF-β1 promoter activity and induces fibronectin and collagen I expression in mouse mesangial cells [16].…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, PAI-1 can activate profibrotic protein synthesis via the uPA receptor [14,16]. We have also observed that recombinant PAI-1 stimulates TGF-β1 promoter activity and induces fibronectin and collagen I expression in mouse mesangial cells [16]. It is possible that PAI-1 antisense ODN-mediated fibronectin protein may be mediated by active suppression of ECM synthesis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Suppression of PAI-1 by siRNA protects affected mice from the development and progression of pulmonary fibrosis (Senoo, Hattori et al 2010). A positive feedback loop between TGF-β and PAI-1 is involved in the development of renal fibrosis in diabetes (Seo, Park et al 2009). TGF-β induces fibronectin and collagen I expression through PAI-1, at the same time PAI-1 activates transcription of TGF-β in mouse mesangial cells (Seo, Park et al 2009).…”
Section: Pai-1 Over Expression In Diseasementioning
confidence: 99%